Microwave Activation: Solventless Catalysed Synthesis of Cross Conjugated Dienones of Tropinone - Renata Gasparova; Didier Villemin; Nathalie Bar (Chemistry Proceedings)
Cross-conjugated dienones are very important biologically active products. The condensation of N-methyl-8-azabicyclo[3.2.1]-bicyclo[3.2.1]octan-3-one (tropinone) with aromatic aldehydes takes place in the presence of acidic (K10 clay, silica) or basic catalysts (alumina, KF-alumina). The best yields of (2E,4E)-2,4-bis-arylmethylene-8-methyl-8-azabicyclo[3.2.1]octan-3-ones were obtained with the K10 clay under microwave irradiation without solvent. New dienones derived from tropinone will be tested in various biological assays.